Genetics - Veer Bala Rastogi (New Delhi MEDTECH, 2019)
Each chapter contains suitable examples, well illustrated diagrams and unsolved questions. The book stands out singly in giving a large number of solved problems. A glossary has been made in end so as to learn the meaning and origin of the words used in the text.
UNIT 1: Genetics- Early Speculations; Birth of Modern Genetics; Post Modelian Genetics; Basic Concepts of Genetics; Fields of Genetics: Genetics in Relation to Other Sciences; Practical Applications of Genetics; Unit-II:- Genetics- Mendel; PreMendelian Experiments; Mendel's Experiments; Mendel's Postulates; Rebirth of Mendelian Genetics; Unit-III:- Genetics-Monohybrid cross and Law of Independent Assortment; Monohybrid Cross; Genetic Terminology; Methods of Derivation of Gamete Types and Genotyope; Mendel's Laws of Inheritance; Unit IV:- Genetics-Dihybrid Cross and Law of Independent Assortment; Dihybrid Cross; Mendel's Law of Independent Assortment; Test Cross for Two Characters; Polyhybrid Cross; Biological Significance of Mendel's Laws; Segregation and Independent Assortment Of Genes in Haploid Species; Distortion of Segregation; Hybrid Vigour Unit V:- Genetics-Probabilityand Stastitical Testing; Introduction; Definition of Probability; Rules of Probability; Calculation of Genetic Ration; Conditional Probability; The Binomial Theorem; Pascal's Triangle.
The text in this book is divided into nine parts. part I Comprises of Classical Genetics or Mendelian Genetics. It deals with the history of Genetics, Mendelian inheritance of characters, Gene Interaction, Polygenic Inheritance, linkage and Crossing Over and Chromosome Mapping. A chapter on Probability and Statistical Genetics has also been added. Part II embraces Sex Determination, Sex-Linked Inheritanceand Cytoplasmic Inheritance. Part III delas with Microbial Genetics; Part IV with Human Genetics and Part V Comprises of Physical Basis of Heredity. Part VI deals with Chemical Basis of Heredity or Molecular Biology Part VII deals with Genetic Engineering or Recombinant DNA Technology. Part VIII deals with Change in Number and Structure of Chromosomes and Gene Mutations. Part IX incorporates Applied Genetics. It gives useful information about Inbreeding, Outbreeding and Hybrid vigour, Applications of genetic Principles to Animal and Plant breeding. Population genetics and Evolution.
Keywords: Molecular Biology- Mendel-Work-Monohybrid Cross- Law of segregation-; Dihybrid Cross- Law ofIndependent Assortment- Probability and Statistical Testing; Gene interaction- Polygenic Inheritance- Blood Groups in Man- Gene & Environment; Sex - Sex linkage- Microbial Genetics- Human Genetics- Heridity- Biotechnology-Cytogenetics-Applied Genetics